Integrative pathway-based survival prediction utilizing the interaction between gene expression and DNA methylation in breast cancer 06 Biological Sciences 0604 Genetics - Kim, So Yeon; Kim, Tae Rim; Jeong, Hyun Hwan; Sohn, Kyung Ah (BMC Medical Genomics, 2018)
Background: Integrative analysis on multi-omics data has gained much attention recently. To investigate the interactive effect of gene expression and DNA methylation on cancer, we propose a directed random walk-based approach on an integrated gene-gene graph that is guided by pathway information. Methods: Our approach first extracts a single pathway profile matrix out of the gene expression and DNA methylation data by performing the random walk over the integrated graph. We then apply a denoising autoencoder to the pathway profile to further identify important pathway features and genes. The extracted features are validated in the survival prediction task for breast cancer patients. Results: The results show that the proposed method substantially improves the survival prediction performance compared to that of other pathway-based prediction methods, revealing that the combined effect of gene expression and methylation data is well reflected in the integrated gene-gene graph combined with pathway information. Furthermore, we show that our joint analysis on the methylation features and gene expression profile identifies cancer-specific pathways with genes related to breast cancer. Conclusions: In this study, we proposed a DRW-based method on an integrated gene-gene graph with expression and methylation profiles in order to utilize the interactions between them. The results showed that the constructed integrated gene-gene graph can successfully reflect the combined effect of methylation features on gene expression profiles. We also found that the selected features by DA can effectively extract topologically important pathways and genes specifically related to breast cancer.
Keywords: Biomarkers, Tumor; Breast Neoplasms; DNA Methylation; Female; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genomics; Humans; Polymorphism, Single Nucleotide; Prognosis; Survival Rate; Transcriptome; Breast cancer; Denoising autoencoder; DNA methylation; Gene expression; Integrative analysis; Multi-omics; Pathway; Random walk